Telemedicine preferences in pediatric urology following the COVID-19 pandemic: A caregiver survey - Bates, Tara; Spray, Beverly; Canon, Stephen (Frontiers in Urology, 2023)
Purpose The COVID-19 pandemic dramatically changed the way many patients interacted with their healthcare providers, with many people being forced to use telemedicine out of necessity. Our study aimed to investigate if this increased usage of telemedicine impacted pediatric patient caregivers’ perception of telemedicine for pediatric urology visits. Materials and Methods A prospective survey was administered to the primary caregiver of all patients less than 18 years of age during either an in-person (IP) or a telemedicine (TM) encounter. The survey included questions regarding accessibility to and opinions toward telemedicine. Results Two hundred, thirty-nine total patient caregivers were surveyed: 209 IP and 30 TM. Most caregivers in both cohorts reported being more likely to use telemedicine now than before the pandemic: IP (125/209, 59.8%) and TM (23/30, 76.7%). Caregivers also reported that the severity of their child’s condition would impact their likelihood to utilize telemedicine for evaluation (IP 162/209 (77.5%) vs. TM 28/30 (93.3%) with caregivers in the TM group even more likely to be influenced by this factor (p = 0.045). Most caregivers in both groups reported that they would utilize telemedicine within 60 miles from the provider. Over 80% of families from both groups reported having both a laptop and a cellular phone in their home. A greater percentage of caregivers in the IP group reported having a desktop computer and a tablet in their home compared to the TM group (41.1% versus 20.0% and 27.3% versus 3.3%, respectively). Conclusions Living through the COVID-19 pandemic has increased the likelihood of caregivers to utilize telemedicine for care of their child’s pediatric urologic disorder. Factors such as severity of illness, distance from the provider, and the context of the evaluation influenced caregiver preferences for utilization of telemedicine. All families surveyed reported having a device at home to perform telemedicine. Laptops and cellular phones were the most commonly used devices.